Rekonvalescentna COVID-19 plazma - Vavić, Nataša; Balint, Bela; Vavić, Neven (Scripta Medica, 2021)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a new human disease. December 31, 2019 marked the day the World Health Organization (WHO) first became aware of an infectious outbreak in the Hubei province in China. Until January 2021, more than two million people died from COVID-19. The use of convalescent plasma (CP) has been widely used in different outbreaks as the first therapeutic option given the lack of effective medications or vaccines, and often as a last chance or experimental treatment. CP is a strategy of passive immunisation. Possible mechanisms of CP-COVID-19 action are antiviral and immunomodulatory. The established protocol for CP-COVID-19 collection defines activities and criteria related to recruiting and informing potential CP donors, clinical and laboratory examination, plasma collection, labelling and storage. Plasma is collected by apheresis/plasmapheresis. Administration of plasma is performed at the request of clinicians, according to the strict indications based on the severity of clinical picture, expressed by precisely determined “scoring” of symptoms. The risks transfusion recipients are likely to be exposed to do not differ from those of standard plasma recipients. At the Blood Transfusion Institute of Serbia, the first plasmapheresis from the recovered patient-donor was performed on 11 April 2020 and so far, collection and distribution of CP-COVID-19 have been performed continuously. During the observation period, preliminary results of the effect of CP transfusion, along with other applied therapy, indicate its favourable effect, both worldwide and in Serbia. CP-COVID-19 should be used as early as possible in the course of infection in order to achieve the best outcomes.